Comprehensive Characterization of Phospholipase C and D Families in Cocoa (Theobroma cacao L.): Identification, Phylogenetics, Gene Structure, and Transcriptomic Insights - Nguyen, Quy Phuong; Tran, Huyen Thi Thanh; Nguyen, Huong Thi Thanh; Dong, Gioi Huy; Ha, Quyen Thi; Vu, Quyen Thi Xuan; Le, Chi Toan; Cao, Phi Bang; Chu, Ha Duc (Bogor Agricultural University, Indonesia, 2025)
This study provides a detailed investigation of the phospholipase C (PLC) and phospholipase D (PLD) gene families in cocoa (Theobroma cacao), focusing on their identification, characterization, and expression patterns. A total of 10 PLC and 12 PLD genes was identified and systematically annotated based on their sequence homology, conserved domains, and functional classification, adhering to established nomenclature. Analysis of physicochemical properties revealed diversity in molecular weights, isoelectric points, and stability parameters, reflecting their structural and functional variability. Phylogenetic analysis classified the genes into distinct subfamilies and highlighted their evolutionary relationships with homologs in Arabidopsis thaliana and rice (Oryza sativa). Gene structure analysis demonstrated significant variation in exon-intron organization, indicating functional specialization and regulatory complexity within these gene families. Expression profiling during cocoa embryo development showed that certain genes, such as TcNPC2, TcPI-PLC5, and TcPLDα1, were highly expressed, while others exhibited stage-specific activity. In response to Phytophthora megakarya infection, several PLC and PLD genes displayed significant changes in expression across different time points and genotypes, including the upregulation of TcPI-PLC2, TcPLDα5, and TcPLDζ2, suggesting their roles in cocoa's stress responses and defense mechanisms. These findings offer new insights into the biological roles of PLC and PLD gene families in cocoa, particularly in growth, development, and stress adaptation, providing a solid foundation for further functional research and potential applications in cocoa improvement programs.